Structuring of Modified Epoxy Composite Materials by Infrared Spectroscopy - Kashytskyi V. P.; Sadova O. L.; Melnychuk M. D.; Golodyuk G. I.; Klymovets O. B. (Журнал інженерних наук)
A comparative evaluation of the structuring processes of the epoxy polymer system with epoxy polymers modified with polyvinyl chloride solution and epoxy composites filled with finely dispersed titanium oxide powder was carried out. Analysis of the infrared (IR) absorption spectra of the studied epoxy polymer and epoxy composite materials showed the presence of deformation and valence vibrations of certain groups of atoms. The oscillations of groups of atoms with double bonds and regions of existence of triple bonds were also revealed. In the region of high frequencies, absorption bands correspond to valence vibrations of groups containing a hydrogen atom. The presence of triple bonds in the epoxy polymer system was determined, indicating unreacted functional groups. This fact corresponds to the low content of the gel fraction of unmodified epoxy polymers after heat treatment and indicates the formation of a system with insufficient chemical bonds. The absorption bands of the epoxy composite material filled with titanium oxide powder are characterized by a lower optical density and a larger peak area compared to the bands of the unmodified epoxy polymer, which indicates the formation of a higher number of crosslinking nodes of the epoxy composite material. The introduction of polyvinyl chloride into the composition of the epoxy polymer system increases the degree of structuring of epoxy polymers. However, a smaller number of formed chemical bonds of the modified epoxy polymer was recorded compared to epoxy composites containing titanium oxide particles. The highest degree of structuring is provided in polyvinyl chloride-modified epoxy composites containing titanium oxide powder due to intensive structuring and formation of double and triple bonds.